2013
DOI: 10.1017/s0007485313000643
|View full text |Cite
|
Sign up to set email alerts
|

The effect of irradiation and mass rearing on the anti-predator behaviour of the Mexican fruit fly, Anastrepha ludens (Diptera: Tephritidae)

Abstract: Fruit flies (Diptera: Tephritidae) are major pests worldwide. The sterile insect technique, where millions of flies are reared, sterilized by irradiation and then released, is one of the most successful and ecologically friendly methods of controlling populations of these pests. The mating behaviour of irradiated and non-irradiated flies has been compared in earlier studies, but there has been little attention paid to the anti-predator behaviour of mass-reared flies, especially with respect to wild flies. Teph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…However, as several of these strains were originated from a single or from very few individuals, a suitable approach could involve the selection on lines with richer genetic pool and the subsequent introgression of the character (cross of strains following by repeated backcrossing). From a practical point of view, candidate characters that potentially increase SIT efficiency include desiccation and/or temperature tolerance (Sørensen et al., ; Tejeda et al., ; Wang, Johnson, Daane, & Nadel, ), avoidance of predators capabilities (Dor, Valle‐Mora, Rodríguez‐Rodríguez, & Liedo, ; Hendrichs & Hendrichs, ; Hendrichs, Wornoayporn, Katsoyannos, & Hendrichs, ; Rao, Aguilar‐Argüello, Montoya, & Díaz‐Fleischer, ) or even the selection of complex and diffuse characteristics such as sexual competitiveness (McInnis, Shelly et al., ; Quintero‐Fong et al., ; Sánchez‐Rosario, Pérez‐Staples, Toledo, Valle‐Mora, & Liedo, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as several of these strains were originated from a single or from very few individuals, a suitable approach could involve the selection on lines with richer genetic pool and the subsequent introgression of the character (cross of strains following by repeated backcrossing). From a practical point of view, candidate characters that potentially increase SIT efficiency include desiccation and/or temperature tolerance (Sørensen et al., ; Tejeda et al., ; Wang, Johnson, Daane, & Nadel, ), avoidance of predators capabilities (Dor, Valle‐Mora, Rodríguez‐Rodríguez, & Liedo, ; Hendrichs & Hendrichs, ; Hendrichs, Wornoayporn, Katsoyannos, & Hendrichs, ; Rao, Aguilar‐Argüello, Montoya, & Díaz‐Fleischer, ) or even the selection of complex and diffuse characteristics such as sexual competitiveness (McInnis, Shelly et al., ; Quintero‐Fong et al., ; Sánchez‐Rosario, Pérez‐Staples, Toledo, Valle‐Mora, & Liedo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that used wild and domesticated fruit flies found that irradiation and mass‐rearing greatly affect sterile fly survival against predators. For example, González‐López et al ., Rao et al . and Dor et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies that used wild and domesticated fruit flies found that irradiation and mass-rearing greatly affect sterile fly survival against predators. For example, González-López et al, 54 Rao et al 55 and Dor et al 56 found that the survival of sterile Mexican fruit fly (Anastrepha ludens) males against their predators is very low compared with their wild counterparts. Similarly, studies on Mediterranean fruit fly showed that sterile males are less likely to evade capture by their predators than wild flies.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason could be their greater activity level. Rao et al (2013) showed that non-irradiated mass-reared A. ludens were less likely to perform a supination to deter the jumping spider Phidippus audax (Hentz) and to avoid it than wild A. ludens . We confirmed that mass-rearing conditions affect the ability of males to avoid predation, as was reported for non-irradiated and irradiated A. ludens males from the bisexual strain and irradiated Tap-7 males (González-López et al , 2016), and C. capitata (Hendrichs et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor, not assessed here, to take into account in the future, is the possible effect of irradiation over the performance of sterile flies, since it has been reported that irradiation can affect survival ability (Hendrichs et al , 2007 for C. capitata ), sexual competitiveness (Rull et al , 2005 for A. ludens ) and anti-predator behaviour (Rao et al , 2013). Also, exposing sterile males to hormonal treatment before release to accelerate sexual maturation (Pereira et al , 2013), and releasing them closer to sexual maturity, to minimize predation before reproduction (McInnis et al , 2013), will be complementary approaches to mitigate the lower predator avoidance and escape abilities of sterile males resulting from mass-rearing conditions.…”
Section: Discussionmentioning
confidence: 99%